Digital media in blended coaching : interaction and distance presence in adult education - Pihlajamäki, Timo (2011)
In this study were studied the dimensions and advantages of the digital media in the adult education and distance presence. The point of view and limiting of the study was coaching and the significance of face-to-face interaction in it. The study was partly based on my three earlier reports about the digital media in the direction of teaching training. Main question of the three reports was would the digital media supply some new dimensions and benefits for teaching training guidance? It was seen, in the reports, as the biggest disadvantage that the distance presence is not a genuine situation because there is lack of (quick) interactivity. The need for a flexible two-way communication channel rose forth in the answers.